Hormone-stimulated modulation of endocytic trafficking in osteoclasts - Stenbeck, Gudrun; Lawrence, Kevin M.; Albert, Anthony P. (Frontiers in Endocrinology, 2012)
A precise control of vesicular trafficking is crucial not only for osteoclastic bone resorption, but also for the crosstalk between osteoclasts and osteoblasts, which regulates bone homeostasis. In addition to the release of growth factors and modulators, such as glutamate, flux through the intracellular trafficking routes could also provide the osteoclast with a monitoring function of its resorption activity. To establish the signaling pathways regulating trafficking events in resorbing osteoclasts, we used the bone conserving hormone calcitonin, which has the unique property of inducing osteoclast quiescence. Calcitonin acts through the calcitonin receptor and activates multiple signaling pathways. By monitoring trafficking of a fluorescent low molecular weight probe in mature, bone resorbing osteoclasts we show for the first time that calcitonin blocks endocytosis from the ruffled border by phospholipase C (PLC) activation. Furthermore, we identify a requirement for polyunsaturated fatty acids in endocytic trafficking in osteoclasts. Inhibition of PLC prior to calcitonin treatment restores endocytosis to 75% of untreated rates. This effect is independent of PKC activation and can be mimicked by an increase in intracellular calcium. We thus define an essential role for intracellular calcium levels in the maintenance of endocytosis in osteoclasts.